Applied geoscience in shale exploration and production - Bartok, Peter, 1947- (PennWell Corporation, 2018)
Since the year 2000, unconventional shale plays have contributed greatly to the global oil and gas supply, particularly in the United States. Understanding and managing these resources requires a unique understanding about the geology, geophysics, rock physics, and rock mechanics of each reservoir in a seamless interdisciplinary approach. Equally important, advanced technologies in seismic and microseismic processing enable professionals to map and identify the hydrocarbon resource and establish the optimum pathways for production. Features and Benefits: Bridging barriers of communication between disciplines; Create an optimal work flow for a shale resource assessment; Achieve a greater understanding of a shale resource potential.